Writing academic articles of interest to practitioners - Peace, Christopher (New Zealand Journal of Health and Safety Practice, 2024)
Professionals (including health and safety practitioners) may be expected to carry out small-scale, applied research that can be shared with others. Writing up and publishing the findings can be hard: Is there an appropriate journal? What do journals expect in manuscripts? Will they publish such research? Drawing on academic and practitioner literature and journal requirements, this article shows how a manuscript meeting those requirements could be structured, written and submitted to a journal to increase the chances of selection for review, revision and publication. The requirements of the New Zealand Journal of Health and Safety Practice, a newly established, practice-oriented journal, are used here to give specific examples of journal expectations.